Mirabegron in female patients with overactive bladder syndrome: What's new? A systematic review and meta-analysis. (August 2020) - Athanasiou, Stavros; Pitsouni, Eleni; Grigoriadis, Themos; Zacharakis, Dimitris; Salvatore, Stefano; Serati, Maurizio
Highlights: Mirabegron improves OAB symptoms and quality of life of female patients with OAB. Mirabegron has similar efficacy compared to anticholinergics. Mirabegron has fewer adverse events compared to anticholinergics. Data are limited regarding mirabegron's impact on women's sexual function. Data are limited regarding mirabegron's long-term use. Abstract: Reviews assessing mirabegron's safety and efficacy, synthesize data from both genders, without providing specific details for female patients with OAB. The aim of this study is to qualitatively and quantitatively synthesize data evaluating mirabegron's use on female patients with OAB. PubMed/Scopus/Cochrane library/Web of Knowledge were searched for full texted, published in English-language and in peer-reviewed journals, up to November 2019, using the keyword "mirabegron".Jadad score modified by adding allocation concealment, MINORS and RoB were used for the Methodological quality and risk of bias assessment. Twenty-one studies were included in this review;7 RCTs, 3 non-RCTs and 11 observational studies. Controlled trials were of unclear (75%), high (12.5%) or serious risk (12.5%) of bias. Twelve weeks of mirabegron use resulted in significant decrease of urgency, frequency, nocturia and UUI by 1.3–2.2, 2.04–2.33, 0.42−0.5 and 0.9–1.04 episodes/24 h, respectively. Quality of life and sexual health was improved significantly. Sexual dysfunction decreased from 98% (84/85) at baseline, to 60% (51/85) after 12-weeks of mirabegron ( p -value < 0.001). Mirabegron had the same efficacy as anticholinergics in improving all OAB symptoms but with fewer adverse events. Hypertension and antimuscarinics' effects (i.e dry mouth, constipation) had an incidence of 2% (28/1221) and 1.9% (23/1221) when mirabegron was administered, respectively. Mirabegron is a safe and effective alternative therapy for females with OAB. However, there is a paucity of high-quality RCTs, with large sample sizes, long-term follow-up focusing on mirabegron's comparison to other therapies, quality of life and sexual health of female patients with OAB.